Multiscale pink‐beam microCT imaging at the ESRF‐ID17 biomedical beamline. (18th August 2020) - Mittone, Alberto; Fardin, Luca; Di Lillo, Francesca; Fratini, Michela; Requardt, Herwig; Mauro, Anthony; Homs-Regojo, Roberto Arturo; Douissard, Paul-Antoine; Barbone, Giacomo E.; Stroebel, Johannes; Romano, Mariele; Massimi, Lorenzo; et al.
Abstract : Details of the implementation of a new tomographic station for pink‐beam imaging at the biomedical beamline ID17 of the European Synchrotron are reported. An overview of the preliminary results obtained using this station is included within this work. Abstract : Recent trends in hard X‐ray micro‐computed tomography (microCT) aim at increasing both spatial and temporal resolutions. These challenges require intense photon beams. Filtered synchrotron radiation beams, also referred to as `pink beams', which are emitted by wigglers or bending magnets, meet this need,  owing to their broad energy range. In this work, the new microCT station installed at the biomedical beamline ID17 of the European Synchrotron is described and an overview of the preliminary results obtained for different biomedical‐imaging applications is given. This new instrument expands the capabilities of the beamline towards sub‐micrometre voxel size scale and simultaneous multi‐resolution imaging. The current setup allows the acquisition of tomographic datasets more than one order of magnitude faster than with a monochromatic beam configuration.